Sosialisasi Peran Dosen dan Mahasiswa dalam Kampus Mengajar Angkatan 4 Tahun 2022 di SDN 03 Sukadana - Aep Saefullah; Elya Nurzanah; Adinda Novita Andhini; Evi Fauziah Mitagani (Yayasan Literasi Sains Indonesia, 2022)
Teaching Campus batch 4 is one of the Free Learning Campus Merdeka (MBKM) programmes launched by the Republic of Indonesia Ministry of Education, Culture, Research, and Technology. Since the Covid-19 pandemic in 2020, this programme has run for three semesters. The Teaching Campus allows students to practise learning outside of the classroom for one semester in order to improve students' literacy and numeracy skills in assigned schools. Students collaborate with teachers to develop learning models and strategies in the target education units. Three female students, accompanied by Field Supervisors, completed the Teaching Campus Program Batch 4 at SDN 03 Sukada, Ciawigebang District, Kuningan Regency. Pre-assignment activities, assignments, work programme implementation, and assignment completion are examples of activities. Students carry out work programmes with the approval of Field Supervisors and the school in order to strengthen literacy, numeracy, digital technology adaptation, and administration for students and SDN 03 Sukadana. The Campus Teaching Program Batch 4 results for students include: (1) being able to improve students' learning literacy abilities in grades 1-6. (2) The ability to improve numeracy learning for both low and high school students. (3) Can improve digital technology adaptation introduction and application in student learning in grades 1-6. (4) Assisting schools in the organisation of classrooms, libraries, and school administration. (5) Has the potential to improve students' character, will, interest, talent, and mentality in learning activities both inside and outside the classroom. Students and Field Supervisors' presence at SDN 03 Sukadana had a significant impact on educational progress; the benefits of the campus teaching programme batch 4 were felt by students, parents, and teachers.